Increased Salience Network Activity in Patients With Insomnia Complaints in Major Depressive Disorder - Liu, Chun-Hong; Guo, Jing; Lu, Shun-Li; Tang, Li-Rong; Fan, Jin; Wang, Chuan-Yue; Wang, Lihong; Liu, Qing-Quan; Liu, Cun-Zhi (Frontiers in Psychiatry, 2018)
Background: Insomnia is one of the main symptom correlates of major depressive disorder (MDD), but the neural mechanisms underlying the multifaceted interplay between insomnia and depression are not fully understood. Materials and methods: Patients with MDD and high insomnia (MDD-HI, n = 24), patients with MDD and low insomnia (MDD-LI, n = 37) and healthy controls (HC, n = 51) were recruited to participate in the present study. The amplitude of low-frequency fluctuations (ALFF) during the resting state were compared among the three groups. Results: We observed ALFF differences between the three groups in the right inferior frontal gyrus/anterior insula (IFG/AI), right middle temporal gyrus, left calcarine, and bilateral dorsolateral prefrontal cortex (dlPFC). Further region of interest (ROI) comparisons showed that the increases in the right IFG/AI reflected an abnormality specific to insomnia in MDD, while increases in the bilateral dlPFC reflected an abnormality specific to MDD generally. Increased ALFF in the right IFG/AI was also found to be correlated with sleep disturbance scores when regressing out the influence of the severity of anxiety and depression. Conclusion: Our findings suggest that increased resting state funcitonal connectivity or other indexes, such as regional homogeneity (ReHo), ALLF or else in IFG/AI may be specifically related to hyperarousal state of insomnia in patients with MDD, independently of the effects of anxiety and depression.